Strategic Approaches to Integrated Pest and Disease Management (IPDM) in Protected Cultivation - Moxichexra, Ablazova; Abzalovich, Zuparov Mirakbar (American Journal of Biomedicine and Pharmacy, 2026)
Protected cultivation systems, while optimizing crop yields, create unique microclimates that facilitate the rapid proliferation of specialized pests and pathogens. This article evaluates strategic approaches to Integrated Pest and Disease Management (IPDM) within greenhouse environments, shifting the paradigm from reactive chemical reliance to a proactive, ecologically based framework. The study analyzes the synergy between cultural practices, such as climate manipulation and sanitation, and the deployment of biological control agents, including predatory mites and microbial antagonists. Furthermore, the integration of modern technologies specifically AI-driven digital scouting and precision sensor monitoring is examined as a means to establish more accurate economic injury thresholds. A significant focus is placed on resistance management through the strategic rotation of bio-rational pesticides to ensure long-term efficacy. By synthesizing ecological principles with technological innovation, this approach aims to reduce synthetic residues, satisfy stringent food safety regulations, and enhance the overall sustainability of protected horticulture. The findings suggest that a multi-layered IPDM strategy not only safeguards crop integrity but also aligns greenhouse production with the increasing global demand for environmentally responsible agricultural practices.